The proteostasis paradox: from systemic collapse in aging to pathway-specific addiction in prostate cancer - Guo, Danhong; Peng, Yaoyao; Yu, Yanlan (Frontiers in Cell and Developmental Biology, 2026)
Aging is the primary risk factor for prostate cancer (PCa), characterized biologically by a systemic collapse of proteostasis networks. Paradoxically, rather than succumbing to this decline, PCa cells exploit it, developing a “proteostasis addiction” to cope with persistent intrinsic stress. This review elucidates this paradox through three conceptual frameworks: the dynamic transition from age-related functional decay to tumorigenic hijacking; the specificity of oncogenic protein regulation; and the functional dichotomy (or “double-edged sword”) of proteostatic components in tumor suppression versus promotion. We examine how declining molecular chaperone networks are co-opted to selectively stabilize the androgen receptor (AR) and its variants. Furthermore, we explore how the ubiquitin–proteasome system (UPS) is re-engineered via E3 ligases and deubiquitinases (DUBs) to orchestrate the precise turnover of tumor suppressors and oncoproteins. Special attention is given to chaperone-mediated autophagy (CMA), which undergoes a reversal from age-associated suppression to hyperactivation in advanced PCa, thereby fueling metabolic adaptation and therapy resistance. Beyond the intracellular context, we discuss how proteostatic imbalances drive the senescence-associated secretory phenotype (SASP) to remodel the tumor microenvironment. Finally, we assess emerging therapeutic strategies, arguing that precision modulation of specific proteostasis nodes—such as distinct E3/DUBs or CMA pathways—represents a promising frontier to overcome castration-resistant prostate cancer (CRPC).